STUDENTS’ RESPONSES TO E-LEARNING SYSTEM: DOES ICT SKILL LEVEL AFFECT? - Iga Setia Utami; Setia Budi; Rini Widyastuti (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
The diversity of university students is a challenge for the use of educational media. This study shows whether ICT skills influence the use of the e-learning system based on the student response. In this case, the e-learning method is a modern way of adding technical features to teaching and learning practices, although it has been initiated and used elsewhere. By doing this study, the lecturers will be able to get an understanding of the reactions of their students using e-learning, so that they can consider implementing this learning system by looking at the level of student ability. This study is a descriptive research. The research instrument consisted of the ICT skills questionnaire and the student impression questionnaire on e-learning. Data was analyzed using a descriptive statistical technique. This study showed that the higher the student ICT skills score, the higher the student experience of e-learning. It can be inferred that there is a major relationship between the degree of ICT skills and student responses to e-learning systems.